HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN PROKRASTINASI AKADEMIK SELAMA PEMBELAJARAN DARING PADA MAHASISWA KEPERAWATAN - Agus Miraj Darajat (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Online learning has positive and negative impacts, one of the negative impacts is causing students to do academic procrastination. One of the factors that influence academic procrastination is family social support. Family social support is an important factor in student self-development in academics because of the need for good communication between parents and children as an effort to reduce academic procrastination. The purpose of this study was to determine the relationship between family social support and academic procrastination during online learning for undergraduate nursing students at Bhakti Kencana University, Bandung.The research method used descriptive correlation, with a cross sectional design. The research population of all undergraduate Nursing students at Bhakti Kencana University was 617 people, a sample of 87 people, using stratified random sampling technique. The research instrument used the Academic Procrastination Scale (APS) and social support distributed using google form to respondents. Data analysis using univariate analysis using mean and bivariate using chi square statistical test.The results showed that most (51.2%) students received less supportive family social support, and most (55.8%) students had a high category of academic procrastination during online learning. The results of the chi square test show -value (0.024) < 0.05, which means that there is a relationship between family social support and academic procrastination during online learning.